DBS in the treatment of Parkinson’s disease - Szeidl, Olga; Szydziak, Joanna; Hrapkowicz, Aleksandra; Janowska, Kinga; Rehan, Dominika; Wołoszczak, Julia; Mioskowska, Agnieszka; Dąbkowska, Daria (Quality in Sport, 2024)
Purpose of the Study: This review examines the role of Deep Brain Stimulation (DBS) as a therapeutic intervention for advanced PD, focusing on indications, patient selection criteria, and potential complications. Materials and Methods: A comprehensive literature review was conducted, analyzing 37 studies from the PubMed database (English-language, up to October 2024) that assess the efficacy, safety, and long-term outcomes of DBS in managing advanced PD symptoms. Basic results: DBS has proven effective in enhancing motor function and quality of life in advanced PD cases. Although generally safe, DBS can present risks, including infections, dyskinesia, and psychiatric side effects. Conclusions: DBS is well known and constantly improving technology. Appropriate patient selection is essential; DBS is generally reserved for patients meeting specific criteria, including a confirmed PD diagnosis, disease duration of more than four years, a positive response to levodopa, and the absence of severe cognitive or unmanaged psychiatric disorders. Emerging research on genetic factors may enhance patient selection in the future.